اتجاه العاملين في المنشآت الرياضية نحو استخدام تكنولوجيا المعلومات، دراسة ميدانية على العاملين في المنشآت الرياضية التابعين لدوان المركب المتعدد الرياضات المسيلة - شريط, خالد; بن شتوح, محمد الامين; د.برباخ, محمد (My University, 2021)
- ملخص الدراسة:  عنوان الدراسة:اتجاه العاملين في المنشآت الرياضية نحو استخدام تكنولوجيا المعلومات، دراسة ميدانية على العاملين في المنشآت الرياضية التابعين لدوان المركب المتعدد الرياضات المسيلة.  أهداف الدراسة: تهدف هذه الدراسة الى التعرف على اتجاه العاملين في المنشآت الرياضية نحو استخدام تكنولوجيا المعلومات باعتبار أن التكنولوجيا اصبحت من المتطلبات الأساسية في عالم التسيير بصفة عامة والتسيير الاداري الرياضي بصفة خاصة، وقد حاولنا في هذه الدراسة التعرف على الفروق في اتجاه العاملين في المنشآت الرياضية نحو استخدام تكنولوجيا المعلومات تعزى للرتبة (مستشار في الرياضة، مربي رئيس في الرياضة، مربي في الرياضة)  مشكلة الدراسة: - ماهواتجاهالعاملينفيالمنشآتالرياضيةنحواستخدامتكنولوجياالمعلومات؟ - هلتوجدفروقفياتجاهالعاملينفيالمنشآتالرياضيةنحواستخدامتكنولوجياالمعلوماتتعزى للرتبة (مستشار في الرياضة، مربي رئيسي في الرياضة، مربي في الرياضة)؟  فرضيات الدراسة: - هناكاتجاهسلبيللعاملينفيالمنشآتالرياضيةنحواستخدامتكنولوجياالمعلومات. - توجدفروقذاتدلالةإحصائيةفياتجاهالعاملينفيالمنشآتالرياضيةنحواستخدامتكنولوجياالمعلوماتتعزىللرتبة (مستشار في الرياضة، مربي رئيسي في الرياضة، مربي في الرياضة).  عينة الدراسة:تم توزيع الاستبيان على 18 عامل.  المنهج:استخدمنا المنهج الوصفي.  أدوات الدراسة:تم الاستعانة باستبيان الذي اعده الدكتور عمار عليمن اجل جمع البيانات نحو الظاهرة المراد دراستها.  النتائج المتوصل إليها: بعد جمع البيانات من عينة الدراسة وعرضها وتحليلها كانت نتائج البحث بالشكل التالي: *كشفتالدراسةالحاليةانهناكاتجاهسلبيللعاملينفيالمنشآتالرياضيةنحواستخدامتكنولوجياالمعلوماتمنخلالالدرجةالكليةللاستبيان *كماكشفتالدراسةعلىعدموجودفروقذاتدلالةاحصائيةفياتجاهالعاملينفيالمنشآتالرياضيةنحواستخدامتكنولوجياالمعلوماتتعزىللرتبة (مستشارفيالرياضة، مربيرئيسيفيالرياضة، مربيفيالرياضة). - الاقتراحات: -تعزيزاتجاهاتالعاملينفيالمنشآتالرياضيةمنأجلتطويرالأداءاتالإداريةالأمثل. -ضرورةتبنياستراتيجياتالتكوينوتعزيزالبنىالتحتيةلتكنولوجياالمعلوماتومحاولةالاستفادةمنتطبيقاتهافيتحسينأداءالمنشآتالرياضية. -توفيرفرصتكوينمستمرةللعمالفيالمنشآتالرياضيةفيمايتعلقبالتسييروالإدارةواستخدامالتكنولوجيا. Abstract: Study title: The tendency of workers in sports facilities towards the use of information technology, a field study on workers in sports facilities of the Office of the Multi-Sports Complex. Objectives of the study: This study aims to identify the attitude of workers in sports facilities towards the use of information technology, given that technology has become one of the basic requirements in the world of management in general and sports administrative management in particular, and we have tried in this study to identify the differences in the direction of workers in sports facilities towards the use of technology Rank information (sports consultant, chief sports educator, sport educator). Study problem: What is the attitude of workers in sports facilities towards the use of information technology? Are there differences in the attitude of workers in sports facilities towards the use of information technology attributable to the rank (sports consultant, master educator in sports, sports educator)? Study hypotheses: There is a negative trend for workers in sports facilities towards the use of information technology. - There are statistically significant differences in the attitude of workers in sports facilities towards the use of information technology due to the rank (consultant in sports, master educator in sports, educator in sports). Sample study: The questionnaire was distributed to 18 workers. Curriculum: We used the descriptive approach. Study tools: A questionnaire prepared by Dr. Ammar Ali was used to collect data on the phenomenon to be studied. Results: After collecting data from the study sample, presenting it and analyzing it, the results of the research were as follows: * The current study revealed that there is a negative trend for workers in sports facilities towards the use of information technology through the total score of the questionnaire * The study also revealed that there are no statistically significant differences in the attitude of workers in sports facilities towards the use of information technology attributable to the rank (consultant in sports, master educator in sports, educator in sports). Suggestions: - Promote the attitudes of workers in sports facilities in order to develop optimal administrative performance. - The need to adopt training strategies and strengthen the infrastructure for information technology and try to benefit from its applications in improving the performance of sports facilities. - Providing continuous training opportunities for workers in sports facilities with regard to management, administration and use of technology.
Keywords: المنشآت الرياضية; تكنولوجيا المعلومات; دوان المركب المتعدد الرياضات المسيلة